ChemInform Abstract: Ruthenium‐Catalyzed Atom‐Economical Stereo‐ and Regioselective Synthesis of Long‐Chain Fatty Acid Enol Esters. Issue 11 (February 2016) - Jena, Rajesh K.; Bhattacharjee, Manish
Abstract: In the presence of the Ru(II) complex, the desired products are available with complete (Z) selectivity.